Post laparoscopic cholecystectomy gastro intestinal bleed - Rajbhandari, Ashish; Bhomi, KK; Pradhan, GB; Shrestha, S; Bhattachan, C L (Journal of General Practice and Emergency Medicine of Nepal, 2011)
Post laparoscopic gastro intestinal bleed accounts for less than 1 % of laparoscopic complications. Here we present a 26 year female who presented with gastro intestinal bleed after 2 weeks of undergoing laparoscopic cholecystectomy. CT scan of abdomen revealed pseudo aneurysm of anterior branch of right hepatic artery. She underwent embolization which revealed pseudo aneurysm of cystic artery and GI bleeding stopped thereafter. She presented 1 month later and had to undergo Laparotomy with the findings of a subphrenic and pelvic collection.